(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
A retrospective study of autopsy cases of fall from height received from South Delhi, during the 10-year period from Jan 1996 to Dec 2005 was conducted at the department of Forensic Medicine, AIIMS, New Delhi. Data was analyzed with regard to the age, gender, location of fall, height of fall, cause of death, pattern of injury. Deaths due to fall from height constitute 5.64% of all medico-legal autopsies conducted during same period. There was a male preponderance with a male: female ratio of 3.8:1 and the age range of victims varied between 4 months to 90 years with a mean of 28.9 years. Maximum number of cases were in the age group of 21 to 30 years (27.11%), followed by 0 to 10 years (21.2%), and 31 to 40 years (19.32%). Accidental deaths made up 97.71%, suicide 2.01%, where as homicide in 0.27% of cases. Head injury (77.04%) was the most common cause of death. Head and face (90.06%) was the prime body region injured. Rooftop (41.6%) was the site from which most people fell down.